EDITORIAL: . - Manninezhath, Thomas (Journal of Dharma, 1991)
Dalit Theology may be unfamiliar to our foreign readers of the Journal of Dharma. But everyone is aware of the contemporary Theologies of Liberation which have been the outcome of the struggles and cry of the poor and oppressed.